Investigation of the effect of shock on the Antarctic meteorites by the 40Ar-39Ar method - Takigami,Yutaka; Kaneoka,Ichiro (1987)
P(論文) In order to investigate the shock effect on the ^<40>Ar-^<39>Ar ages of meteorites, ^<40>Ar-^<39>Ar geochronological studies were performed on two Antarctic meteorites, Y-790964 (LL, shocked) and Y-790448 (LL3,unshocked). Samples were taken from the inner and the outer parts of each meteorite for comparison. The inner part and two outer parts of the seriously shocked Y-790964 have almost the same plateau ages of 1276±24 Ma, 1264±23 Ma and 1241±37 Ma. Older ages are not observed in the higher temperature fractions, which would indicate a very intense shock event. In the unshocked meteorite, Yamato-790448,the plateau-like ages of about 4492 Ma for the inner part and 4325 Ma for the outer part are observed at lower temperatures, but the reason for the apparent difference of the ages is not yet clear. departmental bulletin paper